Tell Me Your Story and I Will Tell Your Sales: A Topic Model Analysis of Narrative Style and Firm Performance on Etsy - Cutolo, Donato; Ferriani, Simone; Cattani, Gino (My University, 2020)
Strategy scholars have widely recognized the central role that narratives play in the construction of organizational identities. Moreover, storytelling is an important strategic asset that firms can leverage to inspire employees, excite investors and engage customers’ attention. This chapter illustrates how advancements in computational linguistic may offer opportunities to analyze the stylistic elements that make a story more convincing. Specifically, we use a topic model to examine how narrative conventionality influences the performance of 78,758 craftsmen selling their handmade items in the digital marketplace of Etsy. Our findings provide empirical evidence that effective narratives display enough conventional features to align with audience expectations, yet preserve some uniqueness to pique audience interest. By elucidating our approach, we hope to stimulate further research at the interface of style, language and strategy.
Keywords: Topic modelling; Narrative; Conventionality; Digital market; Craftsmanship; Etsy; ODS 1 - Fin de la pobreza; ODS 5 - Igualdad de género; ODS 9 - Industria, innovación e infraestructura